Interesse pelo corpo na dialética do esclarecimento de Theodor W. Adorno e Max Horkheimer. - Thiago Ferreira de Borges (2010)
The aim of this study is to present a possibility of exegesis for the important work of Theodor W. Adorno and Max Horkheimer, Dialectic of Enlightenment, 1947, from the presence of the body in the philosophical fragments. The body is the object of special study, which tracked the times and ways as it appears on the main themes of Dialectic of Enlightenment, while it is a kind of "reading key" to the same subjects. Thus, the body switches with the central themes of the work of Adorno and Horkheimer, in positions of a mediator on the one hand and specific object of study by other, as the dynamics of the text so requires.